IMPLEMENTASI GOOD GOVERNANCE DALAM PENGELOLAAN PENDAPATAN DAERAH TAHUN ANGGARAN 2016 (Studi Pada Badan Pengelolaan Keuangan dan Aset Kabupaten Pamekasan) - Rosalina, Amirah (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2018)
The objective of this research is to study the implementation of good governance in the management of regional income at Financial and Asset Management Board of Pamekasan in the budget year of 2016. This study uses qualitative research because this type is more flexible than quantitative research. This study consists of 5 chapters, in which sub-chapters were written to provide a more detailed explanation. The results show that good governance, observed from three points of view i.e. effectiveness and efficiency, accountability, and transparency, in the management of regional income at Financial and Asset Management Board of Pamekasan in the budget year of 2016 is not implemented well.Keyword: Good Governance, Regional Income